UTILIZING MALDI-TOF MS FOR CONFIRMATION OF BACTERIAL ISOLATES IN ROUTINE MICROBIOLOGY ANALYSIS OF FOOD - Prodanov Mirko, Manovska Ratkova Marija, Shikoska Ivana, Cvetkovikj Iskra (My University, 2024)
Food safety is of great importance for global public health. Microbiological contamination and foodborne infections pose a major part of this risk. Consequently, detecting, monitoring, and characterizing pathogens present substantial challenges in quality control environments. The European and the Macedonian regulation have stick rules of the ISO methods that should be used for the testing of food. This are classic microbiological methods witch include culture techniques and biochemical tests, are often recognized for being highly timeconsuming and labor-intensive. The regulation (EU and Macedonian) allows alternative methods only if they are validated according to ISO 16140-6. MALDI-TOF (Matrix-Assisted Laser Desorption/Ionization Time-of-Flight) is a mass spectrometry technique that identifies microorganisms by analyzing their unique protein fingerprints. It works by ionizing proteins in a sample, measuring their mass-to-charge ratio, and comparing the resulting spectra to a database for rapid and accurate identification of bacterial isolates. This method is highly efficient and much faster than traditional culture and biochemical techniques. This method is validated according to ISO 16140-6 for the Salmonella spp. Listeria spp. Listeria monocytogenes and Campylobacter spp. Upon short verification process MALDI-TOF is successfully incorporated in the confirmation of the accredited methods for food borne pathogens in our laboratory. The utilization of this technology in the regular laboratory practice has resulted in shorter reporting time when confirmation is needed, and decrees of the need to reagents for confirmation.